Stability study of composite panels - Toh, Hoong Thiam. (2009)
The buckling behaviour of composite plate, three-strip composite panel in the shape of plain channel and five-strip comf)osite panel in the shape of lipped channel made of symmetric and antisymmetric angle-ply laminates is studied using the Finite Strip Method. The laminated composite panels under study are subjected to in-plane uniform compression load. Three different boundary conditions of the loaded edges are considered. In the first case, both the loaded edges are simply supported. In the second case both the loaded edges are clamped. In the third case, one of the edges is simply supported while the other is clamped. In all cases the unloaded edges of the composite plate are simply supported whereas those of the three-strip composite panel and five-strip composite panel are fi-ee. Displacement function comprises a quintic polynomial in the transverse direction and a 10-term Chebyshev polynomial in the longitudinal direction is chosen to model the out-of-plane deflection. Comparison is made against the displacement fiinction which use trigonometric function in the longitudinal direction. A FORTRAN program has been developed to generate the desired results. The validity of the results obtained are verified by comparing with published results. Geometric parametric studies such as the effect of flange width to web width ratio on the buckling behaviour of composite panels of plain channel and lipped channel shapes is illustrated. In addition, the effect of lip to flange ratio on the buckling behaviour of five-strip composite panel in the shape of lipped channel is also investigated. The advantage of using Chebyshev polynomial over trigonometric function is also discussed.